Graphene chemistry : theoretical perspectives - Jiang, De-en, 1975-; Chen, Zhongfang, 1971- (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2014)
"The aim of this book is to deliver a comprehensive view of graphene chemistry from various perspectives out of theoretical and computational investigations"--
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Graphene; Grafè; Ciència dels materials; TECHNOLOGY & ENGINEERING -- Material Science; Graphene; Electronic books; Llibres electrònics; Electronic books